L’importance de la fonction écologique de la langue quechua - Marina Arratia Jiménez (Lengas)
The importance of the ecological function of the Quechua language is based on the fact that this language encodes an ethnoecological system of knowledge and a biocentric worldview. This form of representation and interpretation means a way to act in that world. This article is based on the research findings carried out in a Quechua speaking andean peasant community, located in a Bolivian geographical area where the greatest biodiversity of tubers is located. Based on the exploration of knowledge about biodiversity of potato, the study reveals the link between territory, culture and language. This connection opens a new perspective for revitalization of indigenous languages, focused on the strengthening of communities and on the environmental protection and restoration of their territories and their traditional productive systems, also considered living spaces of languages.